Dynamic analysis of composition, insecticidal, and antifungal activities of Zanthoxylum armatum DC. at different harvesting periods - Yaqin Peng; Danping Xu; Wenkai Liao; Qianqian Qian; Junhao Wu; Tingjiang Gan; Zhihang Zhuo (Frontiers in Plant Science)
IntroductionEssential oils from plants contain various volatile compounds with antifungal and antioxidant properties. The synthesis and accumulation of these volatile compounds are closely related to factors such as the plant's geographical origin and harvest period. Investigating the insect-repellent and antimicrobial effects of Zanthoxylum armatum DC. essential oils (EOs) at different harvest stages can optimize its harvest and utilization while also promoting the development of eco-friendly agents.MethodsThis study analyzed the changes in the composition and content of volatile compounds in Z. armatum EOs at different growth stages in Nanchong City using GC-MS.ResultsThe results indicate that the accumulation period of volatile compounds occurs before the t5 stage (August 4). Linalool, D-Limonene, and Sabinene were the three most abundant volatile components in the essential oil of Z. armatum pericarp. Many monoterpenes, such as α-Pinene, Sabinene, and β-Myrcene, were found in higher concentrations during the early stages of fruit maturation. Principal component analysis (PCA) revealed a significant difference in volatile composition between the t3, t4, and t5 (t3: July 3, t4: July 18, t5: August 4) stages and the t1, t2, t6, (t1: May 26, t2: June 16, t6: September 9) and t7 (September 28) stages of Z. armatum. Volatile compounds were relatively higher in samples collected in July and August, making these months the optimal harvest period for processing and manufacturing related products. As the fruit of Z. armatum matures, the content of structurally more complex compounds, such as alcohols and esters, increases. The insect-repellent and antifungal experiments demonstrated that Z. armatum EOs exhibited a strong repellent effect against T. castaneum, although the EO’s toxicity was not lethal. The antifungal effect was most pronounced in the EO collected during the t4 stage, where the relative content of various antifungal compounds was higher.DiscussionThis suggests that the antifungal activity of the EOs may result from synergistic or antagonistic interactions among its compounds. By exploring the composition, content, and bioactivities (insect-repellent and antifungal) of Z. armatum EOs at different harvest periods, this study provides theoretical support for developing market-oriented commercial products.